Unveiling the multifaceted antitumor effects of interleukin 33 - Arrizabalaga, Leire; Risson, Aline; Ezcurra-Hualde, Miriam; Aranda, Fernando; Berraondo, Pedro (Frontiers in Immunology, 2024)
Interleukin 33 (IL-33), once predominantly recognized for its pro-tumoral activities, has emerged as a multifunctional cytokine with antitumor properties. IL-33 pleiotropic activities include activation of Th1 CD4 + T cells, CD8 + T cells, NK cells, dendritic cells, eosinophils, as well as type 2 innate lymphoid cells. Regarding this immunomodulatory activity, IL-33 demonstrates synergistic interactions with various cancer therapies, including immune checkpoint blockade and chemotherapy. Combinatorial treatments leveraging IL-33 exhibit enhanced antitumor efficacy across different tumor models, promising novel avenues for cancer therapy. Despite its antitumor effects, the complex interplay of IL-33 within the tumor microenvironment underscores the need for further investigation. Understanding the mechanisms underlying IL-33's dual role as both a promoter and inhibitor of tumor progression is essential for refining therapeutic strategies and fully realizing its potential in cancer immunotherapy. This review delves into the intricate landscape of IL-33 effects within the tumor microenvironment, highlighting its pivotal role in orchestrating immune responses against cancer.